The Circumferential Resection Margin Is a Prognostic Predictor in Colon Cancer - Tang, Xin-Yi; Huang, Meng-Xi; Han, Si-Qi; Chang, Yue; Li, Zhi-Ping; Kao, Xiao-Ming; Chen, Yan-Yan; Liu, Chao; Huang, Ya-Di; Chen, Yi-Tian; Lei, Zeng-Jie; Chu, Xiao-Yuan (Frontiers in Oncology, 2020)
Objective: This study aimed to investigate the potential value of circumferential resection margin (CRM) in colon cancer prognostics. Summary Background Data: CRM has been extensively studied as an important prognostic factor in rectal and esophageal cancer, but not in colon cancer. Methods: Data from 6,681 CRM-positive patients and 25,908 CRM-negative patients diagnosed with colon cancer in 2010-2015 were obtained from the Surveillance, Epidemiology, and End Results database. Statistical analysis methods utilized included the chi-square test, Kaplan‐Meier estimates, Cox proportional and X-tile software analyses. Results: After propensity score matching, CRM positivity was found to be negatively related with survival (P < 0.001). X-tile software identified 0mm and 30mm as optimal cutoff values (P < 0.001) for prognosis, which was applicable only in stage II–IV patients. A 20% and 33% risk decrease were observed in patients with CRM between 0 mm and 30 mm (95% confidence interval (CI) = 0.76–0.84), and larger than 30 mm (95% CI = 0.62–0.71), respectively. Chemotherapy strongly benefited prognosis with a hazard ratio of 0.36 (95% CI = 0.34–0.38) for overall survival (OS). Patients with a CRM value of 0-30mm seemed to benefit most from chemotherapy compared with other groups. CRM and number of regional lymph nodes are independent risk factors, and the latter is a good substitute for CRM in AJCC stage I patients. Conclusion: CRM positivity is a strong unfavorable survival indicator for colon cancer patients. A better outcome is expected with CRM values larger than 30 mm. This cutoff value only applied to stage II-IV patients. For stage I patients, number of regional lymph nodes is a good substitute to predict survival. Chemotherapy was another favorable prognostic factor, especially for patients with a CRM value between 0 mm and 30 mm.